2011
DOI: 10.1242/jeb.050443
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of hemoglobin synthesis in the green anole lizard Anolis carolinensis

Abstract: SUMMARYTetrapod vertebrates possess multiple -and -like globin genes that are ontogenetically regulated, such that functionally distinct hemoglobin (Hb) isoforms are synthesized during different stages of development. The -and -like globin genes of amphibians, birds and mammals are differentially expressed during embryonic development and postnatal life, but little is known about the developmental regulation of globin gene expression in non-avian reptiles. Here we report an investigation into the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…For each individual specimen, Hb isoform composition was characterized by means of alkaline PAGE and/or thin layer isoelectric focusing (PhastSystem, GE Healthcare Biosciences). Depending on the species, the HbA and HbD isoforms were separated by fast protein liquid chromatography (FPLC), DEAE anion-exchange chromatography, CM-Sepharose cation-exchange chromatography, and/or preparative electrofocusing, as described previously (11,36,43,44). The separate isoHbs were further stripped of organic phosphate and other ions by passing the samples through a mixed bed resin column (MB-1 AG501-X8; Bio-Rad) using FPLC.…”
Section: Methodsmentioning
confidence: 99%
“…For each individual specimen, Hb isoform composition was characterized by means of alkaline PAGE and/or thin layer isoelectric focusing (PhastSystem, GE Healthcare Biosciences). Depending on the species, the HbA and HbD isoforms were separated by fast protein liquid chromatography (FPLC), DEAE anion-exchange chromatography, CM-Sepharose cation-exchange chromatography, and/or preparative electrofocusing, as described previously (11,36,43,44). The separate isoHbs were further stripped of organic phosphate and other ions by passing the samples through a mixed bed resin column (MB-1 AG501-X8; Bio-Rad) using FPLC.…”
Section: Methodsmentioning
confidence: 99%
“…In principle, reversible changes can also be produced by cellular changes in Hb isoform composition. All vertebrates possess multiple α-and β-type globin genes, and therefore express multiple, structurally distinct Hb isoforms during different stages of prenatal development and postnatal life (Hoffmann et al, 2010(Hoffmann et al, , 2012Storz et al, 2011aStorz et al, , 2013Storz, 2016b). In this Review, I focus on postnatally expressed Hb isoforms and blood O 2 transport during adulthood [see Brittain (2002) for a discussion of prenatally expressed Hbs and their functional properties].…”
Section: Heterotropic Allosterymentioning
confidence: 99%
“…Multiple rounds of duplication and divergence have produced diverse repertoires of α- and β-like globin genes that are ontogenetically regulated such that functionally distinct Hb isoforms are expressed during different stages of prenatal development and postnatal life (Alev et al 2009; Brittain 2002; Hardison 2001; Hoffmann et al 2008a,b; Opazo et al 2008a,b, 2009; Storz et al 2011b). Surprisingly, however, phylogenetic analyses of the α- and β-globin gene families have revealed that genes with similar stage-specific expression patterns in different species do not necessarily represent 1:1 orthologs that were inherited from a common ancestor (Czelusniak et al 1982; Hoffmann et al 2010b; Opazo et al 2008a; Storz et al 2011a; Opazo et al 2012).…”
Section: Convergent Co-option Of Paralogous Genes For Similar Funcmentioning
confidence: 99%